Faktor Risiko Mortalitas Pneumonia di ICU RS Universitas Kristen Krida Wacana 2021–2024 - Tan, Henny Tannady; Suparto, Suparto; Tanpomas, Irvan; Alfasada, Caesarvio (Universitas Kristen Krida Wacana, 2025)
Pneumonia is an acute infection of the respiratory tract and lung tissue caused by bacteria, viruses, or fungi. Pneumonia can occur at any age and has a high health concern due to its mortality rate and complications. Mortality in pneumonia is influenced by several factors. This study was conducted to determine the risk factors for pneumonia mortality specifically in the intensive care unit of Krida Wacana University Hospital (UKRIDA). A retrospective cohort study was conducted at UKRIDA Hospital using medical records as the data source. The analysis was conducted using the chi-square test. This study involved 122 participants. The results of the analysis showed that there was an association between history of heart disease and mortality of pneumonia patients (p-value 0.014) but age, gender, smoking history, history of type 2 diabetes mellitus, and history of cancer were not associated with mortality of pneumonia patients (p-value > 0.05). Screening and close monitoring need to be done in community pneumonia patients with a history of heart disease for proper management and lower mortality rates.